Physico-chemical properties of ultrafiltered kinnow (mandarin) fruit juice - Ilame S.A.; Singh S.V. (My University, 2025)
Kinnow fruit juice was clarified with ultrafiltration hollow fiber membrane module with cross flow. The surface modified polysulfone based membrane having MWCO 10, 30 and 44 kDa (three cartridges) were used in these studies. The transmembrane pressure drop, cross flow rate and operating condition effects on the quality of the juice have been analyzed. The quality of clarified kinnow fruit juice were evaluated in terms of pH, viscosity, vitamin C, conductivity, total sugar, titratable acidity, TSS, protein, polyphenol, naringin, pectin, pulp content and organoleptic test. The results showed that the membrane with molecular weight cut off 30 kDa was best membrane among the three membranes. The juice could be stored for at least 60 days without any additive. © 2018, Association of Food Scientists & Technologists (India).